(untitled) (University Heart Journal, 2026)
Cardiovascular disease (CVD) remains the leading cause of premature death worldwide, accounting for approximately 20.5 million deaths annually. Chronic coronary syndrome (CCS) is characterized by a chronic mismatch between myocardial oxygen supply and demand, most commonly resulting from atherosclerotic coronary obstruction. Vulnerable coronary plaques, defined by high-risk morphological features on coronary computed tomography angiography (CCTA), are major precursors of acute coronary events. Angiotensin-converting enzyme (ACE), a key component of the renin–angiotensin system, is abundantly expressed in atherosclerotic lesions and macrophages; however, its clinical utility as a serum biomarker for coronary plaque vulnerability has not been previously investigated. Aim of the Study: To evaluate serum ACE as a non-invasive biomarker for identifying vulnerable coronary plaques in patients with chronic coronary syndrome using CCTA as the reference standard. Methods: This cross-sectional study enrolled 30 consecutive adult patients with CCS who underwent CCTA at Bangladesh Medical University (BMU) and Ibrahim Cardiac Hospital & Research Institute, Dhaka, Bangladesh (August 2023–September 2025). Plaque morphology was assessed on a 128-slice SIEMENS SOMATOM CT scanner with ECG-gating. Vulnerable plaque was defined by the presence of at least one high-risk CCTA feature: low-attenuation plaque, positive remodeling, spotty/micro calcification, or napkin-ring sign. Serum ACE activity was measured within 48 hours of CCTA using the kinetic FAPGG hydrolysis method on a Siemens Atelica Solution analyzer. Participants were equally divided into vulnerable-plaque (n=15) and non-vulnerable-plaque (n=15) groups. Diagnostic performance was assessed by receiver operating characteristic (ROC) curve analysis. Results: Among 30 patients with chronic coronary syndrome, 15 had vulnerable coronary plaques and 15 had non-vulnerable plaques on CCTA. Baseline demographic and cardiovascular risk factors were comparable between the groups, with no statistically significant differences observed (all p>0.05). Serum ACE levels were significantly higher in patients with vulnerable plaques compared with those with non-vulnerable plaques (40.02±21.54 vs. 12.56±7.27 U/L, p<0.001). Median serum ACE levels were also markedly elevated in the vulnerable plaque group [36 (24–55) vs. 11 (7–17) U/L, p<0.001]. ROC analysis demonstrated excellent discriminatory performance of serum ACE for identifying vulnerable plaque, with an area under the curve (AUC) of 0.889 (95% CI: 0.769–1.000, p=0.001). A serum ACE cut-off value of ≥20.50 U/L provided the optimal diagnostic performance, yielding a sensitivity of 93.33%, specificity of 86.67%, positive predictive value of 87.50%, negative predictive value of 92.86%, and overall accuracy of 90.00%. Conclusion: Serum ACE is significantly associated with vulnerable coronary plaque in patients with chronic coronary syndrome. It shows strong potential as a non-invasive biomarker for plaque vulnerability and may enhance cardiovascular risk stratification in clinical practice. University Heart Journal 2026; 22(1): 35-40